Teknik Vokal Arttikulasi Lagu “Ngolu Parsorion Sai Muba Do” Pada Paduan Suara SMA Negeri 1 Pagaran Kec.Pagaran - Devi Hartati Pangaribuan; Roy J.M Hutagalung; Aprinaldi P. Simarangkir; Rhyky R.D Sihombing; Rowilson Nadeak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of vocal techniques, especially articulation, in performing the song Ngolu Parsorion Sai Muba Do at SMA Negeri 1 Pagaran choir.The method used I this research is descriptive, where the research describes the findings in the form of written statements and the results of observations in the field. Data collection is carried out through various methods such as observation, documentation, video recording, and observation. This research process involves measuring information directly in the field to produce accurate data that can be analyzed further. Articulation is an important aspect of vocal technique because influences the clarity of the pronunciation of the lyrics and the delivery of the song's meaning to the listener..The application of vocal articulation techniques was carried out through vocal warm-up exercises, vowel and consonant pronunciation exercises, syllable exercises, and direct application to the song Ngolu Parsorion Sai Muba Do. The application of these articulation techniques had a positive impact on the clarity of the pronunciation lyrics, the uniformity of sound between choir’s member, and the improvement of the overall quality of the performance. Thus, it can be concluded that vocal articulation techniques have an important role in improving the quality of song rendition in the SMA Negeri 1 Pagaran choir